POÉTICAS DO FEMININO: A RESSIGNIFICAÇÃO DO BORDADO NA ARTE CONTEMPORÂNEA BRASILEIRA - SANTOS, ANDRESSA RODRIGUES DOS (2021)
The art of embroidery has gone through a process of resignification and reinsertion, with changes led by female artists aiming to address Poetics of femininity, especially from the 1990s onwards in Brazil. The goal of this research project is to analyze how the practice of embroidery presents itself in artworks which focus upon the condition of women in society. Thereby using gender as the main category of analysis. To achieve this, one of the goals is to build an archive that contributed to the status of this activity as feminine, and later, to understand its changes, lead by feminist artistic movements, in contemporary art. By means of bibliographic research, this paper starts off by approaching feminist epistemology, and its intersection with History, Art, and Gender Studies building a theoretic archive for the proposed debate. And given the proposed theme, this work touches on the dichotomy between art and artisanry, to strengthen discussions about representations of characters who practice embroidery, through the iconography of the History of Art, which reveals their connections to femininity, as well as its deprecation in the Art field. And in search for ruptures, following is the comprehension of the artistic resistance movements, exemplified by Judy Chicago and even by the Guerilla Girls collective, which fight for the valorization of art made by women and whose actions contributed to the resignification of embroidery. This investigation culminates in an analysis of the reinsertion of the practice of embroidery by contemporary female artists in the realm of art, such as Rosana Paulino, Beth Moysés and Rosana Palazyan, with the goal of ratifying the hypothesis of the poetic potentiality of embroidery. Such debate becomes present and necessary, considering that women were historically denied access to the making of fine art, and that embroidery has been regarded as feminine and excluded from the field of Art. In line with contemporary discussions of women's rights, the construct of femininity, and gender roles, this work presents itself in the light of Gender Studies. In this sense, this research paper walks through the History of Art, as well as the History of Women, as it also touches on the processes of construction of femininity and its relations to the practice of embroidery in its historic, cultural, and artistic contexts.